The finite element method its basis and fundamentals - Zienkiewicz, O. C. (Elsevier Butterworth-Heinemann, 2005)
Annotation The Sixth Edition of this influential best-selling book delivers the most up-to-date and comprehensive text and reference yet on the basis of the finite element method (FEM) for all engineers and mathematicians. Since the appearance of the first edition 38 years ago, The Finite Element Method provides arguably the most authoritative introductory text to the method, covering the latest developments and approaches in this dynamic subject, and is amply supplemented by exercises, worked solutions and computer algorithms. . The classic FEM text, written by the subject's leading authors . Enhancements include more worked examples and exercises, plus a companion website with a solutions manual and downloadable algorithms .-With a new chapter on automatic mesh generation and added materials on shape function development and the use of higher order elements in solving elasticity and field problems Active research has shaped The Finite Element Method into the pre-eminent tool for the modelling of physical systems.-It maintains the comprehensive style of earlier editions, while presenting the systematic development for the solution of problems modelled by linear differential equations. Together with the second and third self-contained volumes (0750663219 and 0750663227), The Finite Element Method Set (0750664312) provides a formidable resource covering the theory and the application of FEM, including the basis of the method, its application to advanced solid and structural mechanics and to computational fluid dynamics. * The classic introduction to the finite element method, by two of the subject's leading authors * Any professional or student of engineering involved in understanding the computational modelling of physical systems will inevitably use the techniques in this key text * Enhancements include more worked examples, exercises, plus a companion website with a worked solutions manual for tutors and downloadable algorithms.
"In the present edition we have decided not to pursue the course of having three contiguous volumes but rather we treat the whole work as an assembly of three separate works, each one capable of being used without the others ... The two further volumes form again separate books ... The first of these is entitled The Finite Element Method in Solid and Structural Mechanics and the second is a text entitled The Finite Element Method in Fluid Dynamics."--Preface.
Keywords: Finite element method.; Engineering mathematics.; elektronické knihy; electronic books